Enggano As A Hidden Paradise: STP Analysis For Formulating Sustainable Tourism Marketing Strategies - Fitri Khofifah; Heskyel Pranata Tarigan (Journal of Multidisciplinary Research, 2026)
Enggano Island is one of Indonesia’s outermost islands, endowed with rich natural resources, unique cultural heritage, and significant potential for ecotourism development. Despite these advantages, Enggano remains underrecognized in both national and international tourism markets and is less popular compared to similar destinations such as the Mentawai and Siberut Islands. This study aims to analyze the key issues surrounding Enggano’s tourism sector and to propose relevant marketing strategies through the application of the Segmentation, Targeting, and Positioning (STP) framework. The research employs a literature-based and descriptive analysis approach, utilizing secondary data from various sources related to tourism potential, infrastructure conditions, and global tourism trends. The findings reveal that the main challenges include limited accessibility, inadequate digital promotion, and weak integration with international tourism markets. The proposed strategy is to position Enggano as an exclusive ecotourism destination targeting international travelers seeking authentic nature-based experiences, biodiversity research, and sustainable adventure tourism. Through the effective implementation of STP, Enggano Island has the potential to enhance its visibility in the global tourism landscape while simultaneously contributing to sustainable regional economic development.